AB0517 Seasonal Disease Activity in Lupus Nephritis in Northern Portugal – Retrospective Study. (15th July 2016) - Meirinhos, T.; Mariz, E.; Castro Ferreira, I.; Neto, R.; Pereira, E.; Costa, L.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multifaceted autoimmune disease driven by auto-reactive immune cells that target multiple organ systems leading to severe complications. A main complication of SLE is nephritis, formally known as lupus nephritis (LN) that is classified as a secondary form of glomerulonephritis. Exposure to sunlight is one of the environmental factors involved in the pathogenesis of systemic lupus erythematosus. Previous studies of a seasonal influence on SLE activity have conflicting results, suggesting that there was only an increased incidence of photosensitive rashes in the summer months, whereas others found more articular pain in the winter and spring. A study of renal biopsies found that the prevalence of class V lupus nephritis was significantly higher in Winter and Spring. Objectives: To determine, in a cohort of adult LN patients, whether there is any seasonal variation in the activity of LN, and possible correlations between specific organ involvement, gender and disease duration. Methods: Retrospective study, enrolling patients attending a Rheumatology/Nephrology outpatient department, diagnosed with SLE (according to the American College of Rheumatology criteria) and LN. Fixed variables: age, gender, race, disease duration, LN treatment phase, histological classification (renal biopsy), specific organ involvement and therapeutics for SLE, including glucocorticoids. Clinical variables evaluated 2 times for year (one in winter; one in summer, without change in therapeutics): anti-dsDNA antibodies, serum urea and creatinine, urinary sediment and protein-to- creatinine ratio (UPr/Cr). Statistical analysis with Microsoft Excel, version 2010; appropriate statistical tests was used, and a p value<0.05 with a 95% confidence interval will be assumed. Results: 73 SLE patients were enrolled in the study, 61 were female (84%); mean age was 40±11.5 years and mean disease duration was 118±102 months. All the patients were white. 51 patients (70%) had class 4 LN. 58 (79%) patients had extra renal disease, 34 with joint disease and 23 with cutaneous involvement. Mean UPr/Cr was superior in summer than winter (0.443±0.66mg/g Vs 0.401±0.84mg/g), this increase being statistically significant (p=0.04). Patients with SLE cutaneous involvement had higher renal activity in summer and higher seasonal variation (p=0.02). Mean dsDNA was superior in summer, but this difference wasn't statistically significant. No association was identified between seasonal disease activity and sex or disease duration. Conclusions: Despite the reduced size of our cohort, we confirmed a seasonal pattern for Lupus Nephritis and renal disease activity in Northern Portugal, being higher in summer time, in possible correlation with an increase in temperature and duration of sunshine, expecially in SLE patients with cutaneous envolvement. References: Schlesinger N, Schlesinger M, Seshan SV. Seasonal variation of lupus nephritis: high prevalence of class V nephritis during winter and spring. J Rheumatol. 2005; 32:1053–7. Steup-Beekman GM, Gahrmann BM, Steens SC, van Buchem MA, Huizinga TW. Seasonal variation of primary neuropsychiatric systemic lupus erythematosus. J Rheumatol. 2006; 33:1913 – 4. Disclosure of Interest: None declared